An Assessment of Continuous Modeling for Robust Design Flood Estimation in Urban Environments - Ball, James E. (Frontiers in Earth Science, 2020)
Catchment management is a complex task that, over the past decade, has become increasingly important to urban communities. While there are many water related management issues, estimation of the magnitude and likelihood of flood events is one that remains a concern to many mangers of urban drainage systems. Data is an essential component of any approach for estimation of the magnitude and likelihood of design flood characteristics. This data can be obtained from catchment monitoring or catchment modeling with these data sources being complementary rather than competitive. However, the absence of monitored data in urban environments has resulted in the data being obtained predominantly from the use of catchment modeling. Numerous alternative approaches for catchment modeling have been developed; these approaches can be categorized as either single event or continuous models. The philosophical basis behind the use of a continuous modeling approach is the concept that the model predictions will replicate the data that would have been recorded if catchment monitoring were to be undertaken at that location and for the modeled catchment conditions. When using this philosophy, a modeler must determine when the predicted data suitably replicates the true data. Presented herein is an analysis of continuous and event modeling undertaken for design flood estimation in an urban catchment located in Sydney, Australia where monitored data is available to assess the utility of the catchment model. It will be shown that frequency analysis of the predicted flows from the continuous model more closely resemble the frequency analysis of the recorded data.